A novel-shaped THz MIMO antenna with high bandwidth for advanced 6G wireless application - Kamal Hossain Nahin; Jamal Hossain Nirob; Md. Ashraful Haque; Narinderjit Singh Sawaran Singh; Redwan Al Mahmud Bin Asad Ananta; Md. Kawsar Ahmed; Md. Sharif Ahammed; Liton Chandra Paul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This article presents an industrial and innovation highly efficient drone shaped slotted graphene-based multiple input multiple output (MIMO) antenna with improved isolation, designed for high-speed short-range communication, video rate imaging, medical imaging, and explosive detection in the THz band. The proposed antenna is constructed on an 88×244 μm2 polyimide substrate. Key performance parameters such as reflection coefficient, gain, directivity, radiation pattern, and antenna efficiency are evaluated at the resonating frequencies of 1.7 THz, 3.35 THz, and 5.31 THz, covering a wide bandwidth of 4.88 THz with a reflection coefficient of less than -10 dB. The antenna achieves a maximum gain of 13.92 dB and a radiation efficiency of 95.77% within the resonating band. The MIMO design parameters include an envelope correlation coefficient (ECC) of 0.00015, a diversity gain (DG) of 9.9992, and an isolation of less than -31.55 dB between its elements across the entire bandwidth. The outcomes from CST simulations were verified by designing and simulating a similar resistance-inductance-capacitance (RLC) circuit in advanced design system (ADS), with both simulators producing comparable reflection coefficients. These features underscore the potential of the proposed antenna, utilizing simulations and an equivalent RLC circuit model, as a robust candidate for THz band applications in 6G wireless communication.